Sedimentary petrology - Tucker, Maurice E.; Jones, Stuart J. (Wiley, 2023)
"The study of sediments and sedimentary rocks continues to be a core topic in the Earth Sciences and this book provides the reader with a concise account of their composition, mineralogy, textures, structures, diagenesis and depositional environments. The earlier editions of this book have been used by successive generations of students for more than 40 years, and it is the standard text on the subject in many universities throughout the world. This fourth edition is a comprehensive update and expansion of the previous editions with substantially updated new references and suggestions for further reading. The new co-author Stuart Jones has brought his expertise in clastic sedimentology to the rewritten chapters on sandstones and mudrocks. The addition of color images throughout the text enhances the book immeasurably and will aid the student in petrographic work"-- Provided by publisher.